EXPLORING THE ROLE AND IMPORTANCE OF COMPUTER LITERACY IN DEVELOPING CAREER READINESS AT THE UNIVERSITY LEVEL AFTER COVID – 19 - Awais Ali Ch; Rafiullah; Waheedullah; Jamshid ur Rehman; Mohsin Razzaq (International Journal of Contemporary Issues in Social Sciences, 2024)
Because of the COVID-19 outbreak, universities are going digital faster than ever before. This is because the epidemic has changed the way people learn and advance in their careers. As colleges get used to life after the epidemic, it becomes clearer how important computer skills are for getting students ready for work. In light of the recent COVID-19 pandemic, this piece looks at how and why computer literacy is important for getting college students ready for work. For its qualitative approach, the study polled and talked to college students, teachers, and business owners to come up with its results. Computer skills are now an important part of getting a job, and the study looks at how the epidemic has affected this by looking at the points of view of different parties. The data show that knowing how to use computers is now necessary for getting a job after a pandemic. The swift transition to remote learning and telecommuting during the COVID-19 outbreak has amplified the significance of digital skills in various industries. Employers now seek graduates who are proficient in using various digital tools and technologies, from basic office software to advanced programming and data analytics. Furthermore, the study highlights the pivotal role of universities in cultivating computer literacy among their students. By integrating technology-focused coursework and promoting digital fluency across disciplines, universities can better prepare their graduates for the modern workforce. Universities can better prepare students for work by working with businesses to meet the needs of the industry and make it easier for students to go from school to work. On the other hand, the study shows that there are problems with teaching computer skills in higher education. The pandemic and the digital gap have made it harder for students from different socioeconomic backgrounds to achieve the same level of education. Lastly, computer skills have become very important for college students’ job readiness since the COVID-19 epidemic. Students who graduate with a wide range of digital skills will have an advantage in a job market that is getting more and more competitive. To make this happen, schools need to work with businesses, make sure that all kids have fair access to technology, and join the digital age.